A constitutional history of the U.S. Supreme Court - Regan, Richard J. (The Catholic University of America Press, 2015)
Richard Regan presents a concise overview and general history for readers and students in constitutional history and politics, one that will also make an excellent fact-filled source book for lawyers and political scientists. The chapters deal with leading decisions of successive courts and begin with brief biographies of the justices on the courts. Famous cases from Marbury v. Madison, to the Dred-Scott decision, Brown v. Board of Education, Roe v. Wade, up to the Roberts court decision on the constitutionality of Obamacare are discussed. Four appendices deal with the text of the Constitution and amendments, the court system, a chronological list of the justices with biographical details, and a chronological list of the membership on successive courts. Regan devotes more attention to later courts, specifically the Rehnquist and Roberts courts. This is done due to the wealth of material that exists on earlier courts, but also because the decisions of the more recent courts concern developing areas of constitutional law. Finally, extensive treatment of the most recent courts gives great insights into the current Supreme Court justices and their jurisprudence. As any follower of the Supreme Court will perceive, many recent cases involve decisions by a sharply divided court and the concurring and dissenting opinion of the justices make for fascinating and often hard-hitting reading. Regan hopes that an understanding of the individuals who wrote these opinions will help a reader to understand the legal, political and cultural reality of the present-day legal landscape in the United States.